5.006. Показать, что при любом k сумма \(C_{n+k}^{2}+C_{n+k+1}^2\) есть точный квадрат.
Решение.
\(C_n^m = \frac{n!}{(n - m)! m!}\), где \(m \leq n; C_n^0 = 1;\)
\(C_{n+k}^{2}=\frac{(n+k)!}{(n+k-2)!\cdot2!}=\frac{(n+k)(n+k-1)(n+k-2)!}{2\cdot(n+k-2)!}=\frac{(n+k)(n+k-1)}{2}\)
\(C_{n+k+1}^{2}=\frac{(n+k+1)!}{(n+k+1-2)!\cdot2!}=\frac{(n+k+1)(n+k)(n+k-1)!}{2\cdot(n+k-1)!}=\frac{(n+k)(n+k+1)}{2}\)
\begin{multline}
C_{n+k}^{2}+C_{n+k+1}^2=\frac{(n+k)(n+k-1)}{2}+\frac{(n+k)(n+k+1)}{2}=\\
=\frac{(n+k)}{2}\cdot(n+k-1+n+k+1)=\frac{n+k}{2}\cdot(2n+2k)=\\
=\frac{n+k}{2}\cdot 2(n+k)=\frac{n+k}{1}\cdot(n+k)=(n+k)(n+k)=(n+k)^2
\end{multline}
Значит, \(C_{n+k+1}^{2}=(n+k)^2\). Что и требовалось показать.